ANALISIS FAKTOR YANG MEMPENGARUHI MORTALITAS PASIEN NON HEMORRHAGIC STROKE (NHS) DI RSUD TORABELO SIGI SULAWESI TENGAH - Christina Ruminggih; Reni Yuli Astutik; Prima Dewi K (Jurnal Ilmiah Keperawatan IMELDA, 2026)
Non-hemorrhagic stroke is one of the leading causes of mortality and disability that significantly affects patients’ quality of life. Various clinical and comorbid factors are suspected to influence patient mortality, therefore comprehensive analysis is required to identify these determinants. This study aimed to analyze the factors associated with mortality among patients with Non-Hemorrhagic Stroke (NHS) at Tora Belo Regional Hospital, Sigi Regency, Central Sulawesi. This study employed a quantitative design with an analytic observational method using a retrospective approach. The study was conducted from September to October 2025 at Tora Belo Regional Hospital, Sigi Regency, using secondary data obtained from medical records of NHS patients from September 2024 to 2025. The population consisted of 179 patients, and 124 respondents were selected as samples using probability sampling with a simple random sampling technique. Independent variables included systolic blood pressure, diastolic blood pressure, patient treatment time, Glasgow Coma Scale (GCS) score, blood glucose level, cholesterol level, history of diabetes mellitus, and history of heart disease. Confounding variables included age, body mass index (BMI), duration of diabetes mellitus, diabetes complications, and duration of hypertension, while the dependent variable was NHS patient mortality. Data analysis was conducted through univariate analysis, bivariate analysis, and multivariate analysis using linear regression with SPSS version 23.The bivariate analysis showed significant associations between systolic blood pressure (p=0.002), diastolic blood pressure (p<0,001), treatment time (p<0,001), GCS score (p<0,001), blood glucose level (p<0,001), cholesterol level (p=0.003), history of diabetes mellitus (p=0.006), and history of heart disease (p=0.025) with NHS patient mortality. Confounding variables that significantly affected mortality included age (p=0.002), duration of diabetes mellitus (p<0,001), diabetes complications (p=0.047), and duration of hypertension (p<0,001), while BMI showed no significant association (p=0.086). Multivariate analysis indicated that treatment time was the most influential factor associated with NHS patient mortality (p=0.022) with an Adjusted R Square value of 0.331.These findings indicate that clinical and comorbid factors play an important role in the mortality of non-hemorrhagic stroke patients, emphasizing the importance of early detection and prompt management to improve patient survival outcomes.